Managing Fiscal Risks from State-Owned Enterprises - Baum, Anja.; Medas, Paulo; Soler, Alberto; Sy, Mouhamadou (Washington, D.C. : International Monetary Fund, 2020)
Ensuring that state-owned enterprises (SOEs) are efficient and managed prudently is important for economic and social reasons. It is also crucial to contain fiscal risks and reduce the burden on taxpayers from recurrent and large bailouts. Governments need to develop stronger capacity to monitor and mitigate the risks from SOEs. We present a risk tool to benchmark the performance of SOEs relative to their peers and assess their vulnerabilities, including through stress tests. A strategy to mitigate risks requires the right incentives for managers to perform and for government agencies to conduct effective oversight. Incorporating SOEs in overall fiscal targets would promote greater fiscal discipline and transparency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policy